The Impact of Educational Interventions on Nurses’ Perceptions of Parental Support and Attitudes toward Parental Involvement in Neonatal Intensive Care Units - Sawsan Abuhammad; Haneen Barakat; Amat-Alkhaleq Mehrass (International Journal of Clinical Practice)
Aim. To determine the efficacy of interventional programs on nurses’ perceptions of parents’ support and attitudes toward parents’ participation in neonatal care in the neonatal intensive care unit (NICU). Methods. An experimental design was used to determine the efficacy of the interventional program on NICU nurses’ perceptions of parents’ support and attitudes toward parents’ participation in their neonatal care in three hospitals. Nearly 160 nurses from hospitals in North and Middle Jordan participated in the study and were divided into 80 intervention and 80 control groups. Results. The study displayed that nurses had a lower score in the perception of parents’ support and attitude towards their participation in neonatal care in pretest scores than in posttest scores. The mean perception score of parents supported in the control group was 59.17 (SD = 10.1) and in the intervention group was 64.16 (SD = 7.47) (P≤0.01). The mean attitude score of parents’ participation in neonatal care in the control group was 37.08 (SD = 5.76) and that in the intervention group was 38.93 (SD = 5.92) (P=0.04). Conclusion. The results of the study showed a positive impact of the intervention on nurses’ perceptions of parental support and attitudes toward their participation in neonatal care. Moreover, the study found that the only predictor of NPST and PPAS enhancement among nurses was the implementation of an education program.